Evaluasi Jabatan pada Perguruan Tinggi Negeri Badan Hukum - Syihabudhin, Syihabudhin; Wilujeng Suryani, Ani; Fitrah, Akidah; Floressya Arifin, Fatikha (Jurnal Ilmiah Administrasi Publik, 2025)
The purpose of this study is to conduct a job evaluation by determining the job value and job grade at University X using the 10 (ten) sub-factor weighing method. This study is a descriptive research. Data collection methods are carried out by observation, interviews, and documentation. The job profile data collected amounted to 469 positions. The job documents reviewed in this study amounted to 32 positions. The results of the research showed that the job evaluation produced mas the highest job score for the Rector job with a score of 10,387 and the lowest job score for the Operational Services Manager job with a score of 662. The results of the job evaluation obtained 13 jobs grades consisting of 1 job at grade 17, 1 job at grade 15, 3 jobs at grade 13, 2 jobs at grade 12, 4 jobs at grade 10, 2 jobs at grade 8, 3 jobs at grade 7, 3 jobs at grade 6, 1 job at grade 5, 2 jobs at grade 3, and 5 jobs at grade 2. Job value is significantly influenced by Know-How factors, namely technical, managerial and communication competencies. The job value and job grade which are the results of the job evaluation can be used by University X as a consideration for reorganizing employees in accordance with unit specifications and needs, and one of the bases for calculating the value of performance-based incentives.